Lactobacillus isolates from weaned piglets' mucosa with inhibitory activity against common porcine pathogens - Hacin, B; Rogelj, I; Matijasić, B B (Folia microbiologica, 2008)
Twelve lactobacilli isolates from mucosa of 3-5-week-old weaned pigs were found to exert good antimicrobial activity against common porcine pathogens (S. aureus, B. cereus, E. coli, C. perfringens). Two of them produced in addition to lactic acid also considerable amounts of acetic acid, and 6 of them produced hydrogen peroxide and metabolites other than organic acids. Isolates 4/26 and 2/25 (identified as L. crispatus or L. amylovorus) were inhibitory against most strains of S. aureus, B. cereus and E. coli, and especially the strain 4/26 survived well in simulated gastric and intestinal juice. Diarrhea-causing E. coli O8K88H9 Ent(+) was successfully inhibited by the growing culture as well as by the catalase-treated and neutralized supernatant of L. reuteri 12/26. Mucin degradation and multiple resistance to antibiotics were not observed.
Keywords: Feces; Culture Media; Clostridium perfringens; kyselina mléčná; Immunity, Innate; antibiotická rezistence; Lactic Acid; muciny; peroxid vodíku; probiotika; Intestinal Mucosa; Sus scrofa; Ileum; ileum; Swine Diseases; Staphylococcus aureus; Probiotics; přirozená imunita; nemoci prasat; Weaning; Mucins; Escherichia coli; zvířata; feces; kultivační média; střevní sliznice; Bacillus cereus; odstavení; Drug Resistance, Microbial; kultivační média speciální; Hydrogen Peroxide; Lactobacillus; Culture Media, Conditioned; Animals